Analysis Welcoming Expression Used by English Teacher At SMA Negeri 1 Sulabesi Tengah Kabupaten Kepulauan Sula Ternate, North Maluku - Zulkifli Tidore (Sekolah Tinggi Agama Islam Babussalam Sula, 2020)
This article reports the strategies in using welcomimg expression applied by English teacher in teaching and learning process, and the kinds of welcoming expression. The data sources for the research were one English teacher who were teaching english and two students who were studying english from SMA Negeri 1 Sulabesi Tengah.The study employed qualitative approach with a grounded theory method for the research. The data were obtained from several instruments, namely the researcher as the main instrument, observation sheet, list of questions, recorder, and camera to take photo and video. The findings revealed that respondent applied good welcoming expression in the classroom. The results also indicated the students argued that the welcoming expression applied by respondent was very good and effective.